Effect of Mechanical Vibrations on Human Body - AlShabi Mohammad; Araydah Walaa; ElShatarat Hani; Othman Mohammad; Bani Mohammed; Gadsden Stephen Andrew (My University, 2016)
Mechanical vibrations cause forces that affect human bodies. One of the most common positions for human bodies is the seated position. In this work, mathematical models of the seated human body are investigated and simulated in a Simulink/ MATLAB environment. In addition, segments of the human body are studied and models are developed and built by using Simulink/MATLAB. As part of this work, model analysis and state-space methods are used in order to check and validate the results obtained from the simulations. Two types of forces are used to test the whole seated human body under low frequency citation. The first is a sinusoidal wave signal based on literature, and the second is an impulse function. The effects of mechanical vibration on the head and lumbar are studied as these parts of the human body are usually the most effected areas. Kinematic states of the head segment and lumbar are considered. The characteristics of the vibration response on the two segments are also obtained. In addition to the mechanical vibrations study, this paper is a resource for the development and implementation of models in the Simulink/MATLAB environment
Keywords: Vibration; Human Body; MATLAB; State-Space